2022
DOI: 10.1177/15579883221095387
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Obesity and Overweight Disparities Among Sexual Minority Men: A Meta-Analysis

Humberto López Castillo,
Christopher W. Blackwell,
Eric W. Schrimshaw

Abstract: This study aims to analyze the prevalence and likelihood of overweight, obesity, and elevated body mass index (BMI) among sexual minority men (i.e., men who have sex with men [MSM], men who have sex with men and women [MSMW], and all sexual minority men), using men who have sex with women (MSW) as the reference group. Studies reporting mean BMIs or prevalence or likelihood of obesity, overweight, or elevated BMI categorized by sexual orientation were included. Data were pooled and analyzed to report mean diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 86 publications
1
1
3
Order By: Relevance
“…Consistent with prior work, we found that with the exception of a higher prevalence of tobacco use, gay male individuals have more favorable scores for diet, BMI, and glycemic status scores than heterosexual male individuals . Our findings are consistent with the few studies that have used the Healthy Eating Index to examine diet quality among gay men .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with prior work, we found that with the exception of a higher prevalence of tobacco use, gay male individuals have more favorable scores for diet, BMI, and glycemic status scores than heterosexual male individuals . Our findings are consistent with the few studies that have used the Healthy Eating Index to examine diet quality among gay men .…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, gay men report higher levels of physical activity and better diet quality than heterosexual men . Similarly, several studies have shown that gay men have lower risk of obesity, hypertension, and diabetes …”
Section: Introductionmentioning
confidence: 99%
“…The distribution of BMI among SGMs compared to heterosexuals was inconsistent with previous Western studies. 34,35 Interestingly, this study showed the opposite of the association that homosexual and bisexual females tended to be overweight/obese 34 , and SGM males were less likely to be overweight/obese. 35…”
Section: Discussioncontrasting
confidence: 61%
“…34,35 Interestingly, this study showed the opposite of the association that homosexual and bisexual females tended to be overweight/obese 34 , and SGM males were less likely to be overweight/obese. 35…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation